1975
DOI: 10.1007/bf00431181
|View full text |Cite
|
Sign up to set email alerts
|

Four endoparasitic nematode destroying fungi isolated from Sand Ridge State Forest soil

Abstract: A survey to determine the endoparasitic nematode destroying fungi located within Sand Ridge State Forest of Illinois was conducted from 1 January to 3 April 1973. A total of seven nematode destroying fungal species were isolated from the collected soil samples. Harposporium helicoides, H. crassum, H. lilliputanum are endoparasitic nematophagous fungi that have been isolated previously from the forest soil. Acrostalagmus gonoides, A. obovatus, Cephalosporium balanoides, and Monacrosporium cionopagum are nematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…There have been numerous surveys on the occurrence of nematophagous fungi, which have shown that the group is found throughout the world and in all types of climate. The most notable surveys have been conducted in North America: in the U.S.A. in Maryland (Drechsler, I 937, I 95ob), Oregon (Tolmsoff, 1959), Florida and North Carolina (Feder, 1962), California (Mankau & Clark, 1959) and Illinois (Monoson & Williams, 1973; Monoson, Conway & Nelson, 1975); and in Canada in Quebec (Estey & Olthof, 1965) and Ontario (Barron, 1978). Throughout Europe: in England (Duddington, 1940(Duddington, , 1946(Duddington, ,1950(Duddington, ,1g51 a, b, 1954Juniper, 1957); Scotland (Mackenzie, 1960); Ireland (Gray, 1983a; Italy (Verona & Lepidi, 1970); Poland (Jarowaja, 1963); Germany (Fritsch & Lysek, 1983); France (Comandon & DeFonbrune, 1938; Virat, 1977;Peloille, , 1981Peloille & Cayrol, 1979); U.S.S.R. (Soprunov & Galiulina, 195 I ;Soprunov, 1958;Kondakova, 1960;Mekhtieva, 1972); Denmark (Shepherd, 1956) and Finland (Ruokala & Salonen, 1967; Salonen & Ruokola, 1968 (Kuthubutheen, Muid & Webster, 1985); Japan (Miura, 1973;Mitsui, 1983 ; 1985 ; Kobayashi & Mitsui, I 975).…”
Section: Ecology Of Nematophacous Fungi ( I ) Distributionmentioning
confidence: 99%
“…There have been numerous surveys on the occurrence of nematophagous fungi, which have shown that the group is found throughout the world and in all types of climate. The most notable surveys have been conducted in North America: in the U.S.A. in Maryland (Drechsler, I 937, I 95ob), Oregon (Tolmsoff, 1959), Florida and North Carolina (Feder, 1962), California (Mankau & Clark, 1959) and Illinois (Monoson & Williams, 1973; Monoson, Conway & Nelson, 1975); and in Canada in Quebec (Estey & Olthof, 1965) and Ontario (Barron, 1978). Throughout Europe: in England (Duddington, 1940(Duddington, , 1946(Duddington, ,1950(Duddington, ,1g51 a, b, 1954Juniper, 1957); Scotland (Mackenzie, 1960); Ireland (Gray, 1983a; Italy (Verona & Lepidi, 1970); Poland (Jarowaja, 1963); Germany (Fritsch & Lysek, 1983); France (Comandon & DeFonbrune, 1938; Virat, 1977;Peloille, , 1981Peloille & Cayrol, 1979); U.S.S.R. (Soprunov & Galiulina, 195 I ;Soprunov, 1958;Kondakova, 1960;Mekhtieva, 1972); Denmark (Shepherd, 1956) and Finland (Ruokala & Salonen, 1967; Salonen & Ruokola, 1968 (Kuthubutheen, Muid & Webster, 1985); Japan (Miura, 1973;Mitsui, 1983 ; 1985 ; Kobayashi & Mitsui, I 975).…”
Section: Ecology Of Nematophacous Fungi ( I ) Distributionmentioning
confidence: 99%
“…Nematodes-destroying fungi have been isolated from soil in Illinois in 1975 (Monoson, Conway, & Nelson, 1975) and in England as early as 1954 (Duddington, 1954). Selection and isolation of microfungi for use in biological control of parasitic nematodes in animals has been patented in 1997 (patent number US5643568 A).…”
Section: History Discovery and Benefits Of Nematodes-destroying Fungimentioning
confidence: 99%
“…The farm soils studied by Diirschner [3] showed a high number of Cephalosporium balanoides and, to a lesser extent, Meria coniospora. The genus Harposporiurn must be regarded separately, since its species are isolated regularly [3][4][5][6]: Harposporium anguillulae and Harposporium oxycoracum seem to exclude one another in beech-wood podzol and lowland soils, as is shown by the differences between the results of Fritsch and Lysek [6] and the results of this study; Monoson found the species Harposporium helicoides, Harposporium crassum and Harposporium lilliputanum in different wood soils in Illinois, U.S.A. [4,5]. Due to the widespread occur-rence of this genus, its species may prove useful in the search for correlations between endoparasitic nematode-destroying fungi and soil factors.…”
Section: Dependence On Soil Factorsmentioning
confidence: 99%
“…Cooke [2] has stated that there may be marked differences between the predacious activity exhibited in cultures and that in the natural habitat. Estimations of the number of species or infections in the soil have been made by Diirschner [3] and by Monoson and colleagues [4,5]. To obtain further information about the quantity and activity under natural conditions, the number and density of nematode-destroying endoparasitic fungi were estimated at different sites in West Berlin.…”
Section: Introductionmentioning
confidence: 99%